2019
DOI: 10.1016/s0140-6736(19)30648-8
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting gender norms in health systems: making the case for change

Abstract: ContributorsKH and AR led conceptualisation and drafting of the paper. AD led the study on nurses in Uttar Pradesh, ND the study on accredited social health activists in Uttar Pradesh, HW and JR the study on community health workers and community health worker policy in Sierra Leone, LM, JK, and AR the study on gender parity in the global physician workforce, and KH, YA, and NS the study on selfhelp groups in India. FS and RF-M led development of the case on the nurse from eSwatini. VP, RH, and EBa did the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
205
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(227 citation statements)
references
References 150 publications
(186 reference statements)
7
205
0
15
Order By: Relevance
“…In order to design effective intervention to improve male partner engagement, we have to recognise wider Malawian gender orders and gender norms around masculinities [54]. Such "restrictive gender norms" [55] and the wider societal inequality regimens [56] are reproduced in the healthcare systems [57] and may impact male partner engagement. As Hay K et al [55] showed that gender norms and inequities are determined and reinforced in families, communities, structures and policies and perpetuated by institutions including healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to design effective intervention to improve male partner engagement, we have to recognise wider Malawian gender orders and gender norms around masculinities [54]. Such "restrictive gender norms" [55] and the wider societal inequality regimens [56] are reproduced in the healthcare systems [57] and may impact male partner engagement. As Hay K et al [55] showed that gender norms and inequities are determined and reinforced in families, communities, structures and policies and perpetuated by institutions including healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Such "restrictive gender norms" [55] and the wider societal inequality regimens [56] are reproduced in the healthcare systems [57] and may impact male partner engagement. As Hay K et al [55] showed that gender norms and inequities are determined and reinforced in families, communities, structures and policies and perpetuated by institutions including healthcare systems. Previous studies in Malawi suggest that gender norms and masculinities [41] are factors in access, attitudes and stigma [54,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, emergency systems development, research, education, workforce growth, and sustainability can all serve to empower women by increasing access to resources, by strengthening women’s sense of agency and self‐efficacy, and by providing a means of achievement and advancement. Further, research suggests that confronting restrictive gender norms and inequities in health systems development, particularly in these early stages, can impact outcomes and community health more broadly …”
Section: Empowering Women Through Emergency Care Development In Lmicsmentioning
confidence: 99%
“…This special collection in the Journal of Global Health builds on the evidence base linking gender norms and health, presenting findings to advance our thinking about these interconnected systems [1,2,6,9,10]. The collection takes a general focus on three areas: (1) sexual and reproductive health, (2) adolescent populations, and (3) health policy.…”
mentioning
confidence: 99%